2021
DOI: 10.1093/neuros/nyaa544
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Radiosurgery for Perioptic Meningiomas: An International, Multicenter Study

Abstract: BACKGROUND Stereotactic radiosurgery (SRS) is increasingly used for management of perioptic meningiomas. OBJECTIVE To study the safety and effectiveness of SRS for perioptic meningiomas. METHODS From 12 institutions participating in the International Radiosurgery Research Foundation (IRRF), we retrospectively assessed treatment parameters and outcomes followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Although optic nerves, chiasm and optic tracts, as well as all sensory cranial nerves, are the most sensitive neural structures, RION is reported as being a rare complication. 6,[14][15][16]20 Mayo C et al 29 found that the incidence of RION was negligible for doses below 10-12 Gy in RS. Nevertheless, limited data exist about tolerance doses for fractionated high-dose treatments like hypo-RS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although optic nerves, chiasm and optic tracts, as well as all sensory cranial nerves, are the most sensitive neural structures, RION is reported as being a rare complication. 6,[14][15][16]20 Mayo C et al 29 found that the incidence of RION was negligible for doses below 10-12 Gy in RS. Nevertheless, limited data exist about tolerance doses for fractionated high-dose treatments like hypo-RS.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to these features, RS could prove to be an effective and safe treatment for meningioma due to its inherent ability to deliver a sharply focused highdose radiation to a solitary target, while sparing normal surrounding tissues. 6,19,20 Literature data on RS show tumor control rate at 10 years ranging from 71% to 97.2% 5 and an improvement of pre-existing cranial nerve deficits in 70% to 100% of patients with small to medium-size lesions. However, for relatively large-sized lesions or for those in close relation to cranial nerves and vascular structures, 21 RS provided lower results, both in primary and adjuvant setting.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggest using higher margin doses (> 13 Gy) to achieve better local control ( 34 ). For patients receiving SRS, a single dose of 14-18 Gy is typically used at most radiation centers for similar local control, while doses ≤ 12 Gy are associated with poorer local control rates ( 35 ), and doses ≥ 10 Gy to the optic apparatus are associated with decreased vision after SRS ( 36 ). Low fractionated treatment for meningiomas around the optic nerve can deliver SRS doses of 19.5 Gy/3 fractions and 25 Gy/5 fractions to the optic pathway while still maintaining a lower risk of optic neuropathy and the typical range for radiation therapy margin doses in WHO grade 3 meningiomas are 18 to 24 Gy ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…While chemotherapy has been documented to improve survival in malignant lesions, radiotherapy as a primary or adjuvant modality aims mainly to halt tumor progression. Studies that investigated the efficacy of radiotherapy for meningiomas and schwannomas reported high 10-year PFS rates of up to 90–98% [ 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ]. However, since different tumor types respond differently to various modalities, it is essential to tailor a personalized management plan based on the patient tumor pathology and their clinical condition.…”
Section: Discussionmentioning
confidence: 99%